Agricultural Development: Production, Policy, and Institution Nexus in Perkin’s Framework - Dwi Nur Laili Paramita; Febria Risma Wardah; Syauqi Agung Firmanda; Purna Pria Atmaja (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2025)
Background: The agricultural sector faces several challenges, including low productivity, high production costs, and unsupportive policies, which hinder the sector's full potential. This article examines the roles of technology, government policy, and institutions in promoting agricultural development, based on a literature review of the book Economics of Development by Perkins et al. (2013). Aim: This study aims to elucidate the importance of agricultural sector growth and modernization. Methods: This review employs the Literature Review method, drawing upon various scholarly sources related to Agricultural Development and other relevant literature to serve as references and comparative material for the discussion. Results: The review finds that technological innovation and institutional capacity consistently emerge as the most decisive mechanisms for agricultural modernization, while policy effectiveness shows mixed evidence across different contexts. Although there is broad agreement that agricultural growth strongly contributes to poverty reduction, divergence remains regarding the extent to which trade liberalization benefits smallholder farmers. Conclusion: Therefore, an integrated policy approach, the use of appropriate technologies, and the strengthening of institutional frameworks are essential strategies to maximize the agricultural sector’s contribution to economic development and poverty alleviation.